Performance characteristics of a new competitive DQ2.5-glia-α3 gliadin ELISA. (April 2020) - Sajic, Nermin; Oplatowska-Stachowiak, Michalina; Streppel, Lucia; Drijfhout, Jan Wouter; Salden, Martin; Koning, Frits
Abstract: An inter-laboratory study with 15 participating laboratories was performed to determine the performance characteristics of a rapid and simple competitive DQ2.5-glia-α3 Gliadin ELISA for the detection of gluten in food. The ELISA test kit used in this study was previously validated in an intra-laboratory study showing excellent performance for determination of gluten in processed foodstuffs such as sauces, soups and beers. The participants of the inter-laboratory study obtained 20 samples and were asked to analyse them in accordance with the ELISA's manual. The samples included in this study were oats and gluten-free tomato soup powder spiked with gliadin standard obtained from the Working Group on Prolamin Analysis and Toxicity and 12 wheat starch samples naturally contaminated with gluten. The spiked samples were prepared by adding 10, 50 and 100 ppm of gliadin, what corresponds to 20, 100 and 200 ppm of gluten, respectively. Non-spiked samples were also provided. The spiking levels were chosen to test the ELISA performance with samples containing gluten at the concentrations relevant for the labelling requirements. In accordance with Commission Implementing Regulation 828/2014 foodstuffs containing maximum of 20 ppm and 100 ppm can be labelled "gluten-free" and "very low gluten", respectively. In case of spiked samples, the participants obtained average recoveries of PWG-gliadin from spiked oats and gluten-free tomato soup powder of 84.8–102.8% and 88.6–103.5% at all 3 spiking levels respectively. There was also a good agreement between the average results obtained in this study, LC-MS-MRM results and R5 sandwich ELISA reference method results for naturally contaminated wheat starch samples. This inter-laboratory study demonstrated the applicability of DQ2.5-glia-α3 Gliadin ELISA for the quantitative screening of foodstuffs for the presence of gluten. Highlights: DQ2.5-glia-α3 ELISA for gluten detection was validated in a collaborative study. A set of 20 samples of oats, tomato powder soup and wheat starch were analysed. A good correlation between the results obtained by all 15 participants was found. A good correlation between DQ2.5-glia-α3 and R-5 sandwich ELISAs results was found.